2015
DOI: 10.1136/bmjopen-2014-006874
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-led management of chronic pain in primary care: costs and benefits in a pilot randomised controlled trial

Abstract: ObjectivesTo explore differences in mean costs (from a UK National Health Service perspective) and effects of pharmacist-led management of chronic pain in primary care evaluated in a pilot randomised controlled trial (RCT), and to estimate optimal sample size for a definitive RCT.DesignRegression analysis of costs and effects, using intention-to-treat and expected value of sample information analysis (EVSI).SettingSix general practices: Grampian (3); East Anglia (3).Participants125 patients with complete resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 25 publications
0
67
0
Order By: Relevance
“…Reviewing by title and abstract excluded 158 studies that were not RCTs. The full texts of the remaining 3 trials [ 26 28 ] were examined in detail and evaluated as meeting the inclusion criteria. A further article [ 29 ] retrieved when examining the reference lists of retrieved studies was included as it presented additional data to an included RCT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewing by title and abstract excluded 158 studies that were not RCTs. The full texts of the remaining 3 trials [ 26 28 ] were examined in detail and evaluated as meeting the inclusion criteria. A further article [ 29 ] retrieved when examining the reference lists of retrieved studies was included as it presented additional data to an included RCT.…”
Section: Resultsmentioning
confidence: 99%
“…A further article [ 29 ] retrieved when examining the reference lists of retrieved studies was included as it presented additional data to an included RCT. The data from the two articles were considered as one pilot trial (The PIPPC pilot trial) [ 26 , 29 ]. Therefore, 3 trials (2 definitive trials and 1 pilot trial) were included ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot randomized study performed in the United Kingdom in patients receiving regular prescribed medication for pain (at least two acute and/or one repeated prescriptions within the four previous months) showed that pharmacist‐led medication based on medication review and feedback to the GP was associated with a cost increase of £54 per patient when compared with GP‐led treatment as usual. The difference reached £77 per patient when pharmacist intervention included prescribing instead of feedback to GP (Neilson et al, ). The benefits for patients assessed as quality‐adjusted life years (QALYs) at 6 months were similar in the three arms.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be necessary to implement changes at scale in order to see cost savings; one pilot study of pharmacist-led chronic pain management resulted in increased costs compared with usual care. 21 …”
Section: Cost Effectivenessmentioning
confidence: 99%